Professional C++, third edition - Gregoire, Marc (Wrox, 2014)
From game programming to major commercial software applications, C++ is the language of choice. It is also one of the most difficult programming languages to master. This third edition, substantially revised and revamped, shows experienced developers how to master the latest release of C++. More advanced language features and programming techniques are presented. Discover how to navigate the significant changes to the core language features and syntax, and extensions to the C++ Standard Library and its templates. This practical guide details many poorly understood elements of C++ and highlights pitfalls to avoid. Coverage includes: best practices for programming style, testing, and debugging; working code that readers can plug into their own apps; in-depth case studies with working code; and tips, tricks, and workarounds with an emphasis on good programming style. --